Dampak Toxic Digital Culture terhadap Perilaku Organisasional dan Turnover Intention di Lingkungan Kerja Digital - Metris, Diksi; Azis, Nur; Rasyiddin, Ahmad (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2026)
The development of digital technology has changed the way we work, but it has also brought new challenges such as a toxic digital culture, which can negatively impact organizational behavior and employees' intentions to leave their jobs. This research aims to analyze how unhealthy digital culture affects employee motivation, engagement, and the desire to leave the organization. This research uses qualitative methods, with data analysis based on literature review and documentation studies from various relevant sources. Unlike previous research that heavily relied on interviews and observations, this study explores the phenomenon of toxic digital culture through conceptual mapping and theoretical analysis. The research results show that digital overload, lack of work-life balance, and high work pressure due to instant communication expectations can increase employee stress and decrease job satisfaction. As a result, employees become less productive, experience conflicts within teams, and are more likely to have a desire to leave the company. The conclusion of this research emphasizes that toxic digital culture is an important factor that needs to be addressed in digital organization management. Companies need to implement healthy communication policies, support employee well-being, and create a more balanced work environment to reduce the negative impact of digital culture on employee retention.